2010
DOI: 10.1128/jb.01826-08
|View full text |Cite
|
Sign up to set email alerts
|

Bistable Expression of CsgD in Biofilm Development ofSalmonella entericaSerovar Typhimurium

Abstract: Bacterial persistence in the environment and in the infected host is often aided by the formation of exopolymer-enclosed communities known as biofilms. Heterogeneous gene expression takes place in microcompartments formed within the complex biofilm structure. This study describes cell differentiation within an isogenic bacterial cell population based on the example of biofilm formation by Salmonella enterica serovar Typhimurium. We analyzed the expression of the major biofilm regulator CsgD at the single-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
114
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 56 publications
8
114
0
3
Order By: Relevance
“…2 and 3). Studies in S. typhimurium have previously demonstrated that levels of CsgD and curli can vary from cell to cell in bacterial communities (17,49). Here we have demonstrated a distinct bimodal restructuring in which matrix-producing bacteria line the air-biofilm interface, and non-matrix-producing bacteria fill the wrinkle interiors.…”
Section: Discussionmentioning
confidence: 60%
“…2 and 3). Studies in S. typhimurium have previously demonstrated that levels of CsgD and curli can vary from cell to cell in bacterial communities (17,49). Here we have demonstrated a distinct bimodal restructuring in which matrix-producing bacteria line the air-biofilm interface, and non-matrix-producing bacteria fill the wrinkle interiors.…”
Section: Discussionmentioning
confidence: 60%
“…The bacterial secondary messenger c-di-GMP is known to play a role in regulating csgD transcription and CsgD activity (30,31). High levels of c-di-GMP are associated with biofilm formation, whereas low levels are associated with a single-cell lifestyle (44).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the cells in the fluid phase, there were cells that formed an adherent biofilm at the air-liquid interface of the culture flask. These cells differed in terms of oxygen availability (30), and the amount of biofilm formed was highly variable (data not shown); therefore, they were excluded from further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations